2022
DOI: 10.2147/cmar.s368381
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Non-Rhabdomyosarcoma Soft Tissue Sarcomas: Standard of Care and Treatment Recommendations from the European Paediatric Soft Tissue Sarcoma Study Group (EpSSG)

Abstract: This paper describes the standard of care for patients with non-rhabdomyosarcoma soft tissue sarcomas (NRSTS) and the therapeutic recommendations developed by the European paediatric Soft tissue sarcoma Study Group (EpSSG). NRSTS form a very mixed group of mesenchymal extraskeletal malignancies. Their rarity, heterogeneity, and aggressiveness make the management of children and adolescents with these tumors complex and challenging. The overall cure rate for patients with NRSTS is around 70%, but survival depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 136 publications
1
36
0
5
Order By: Relevance
“…There was a nonsignificant trend toward higher EFS and OS and a lower risk of tumor spillage in patients operated after neoadjuvant chemotherapy. This result is similar to the results published by the SIOP group for Wilms’ tumor and hepatoblastoma compared to the North American approach of upfront surgical resection 10,11 . Similarly, the ARST00332 study focusing on NRSTS identified the risk of increased marginal resection rate with upfront compared to delayed resections, although without impact on survival 9 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There was a nonsignificant trend toward higher EFS and OS and a lower risk of tumor spillage in patients operated after neoadjuvant chemotherapy. This result is similar to the results published by the SIOP group for Wilms’ tumor and hepatoblastoma compared to the North American approach of upfront surgical resection 10,11 . Similarly, the ARST00332 study focusing on NRSTS identified the risk of increased marginal resection rate with upfront compared to delayed resections, although without impact on survival 9 .…”
Section: Discussionsupporting
confidence: 84%
“…This result is similar to the results published by the SIOP group for Wilms' tumor and hepatoblastoma compared to the North American approach of upfront surgical resection. 10,11 Similarly, the ARST00332 study focusing on NRSTS identified the risk of increased marginal resection rate with upfront compared to delayed resections, although without impact on survival. 9 The effects of primary versus delayed resection were not assessed in the North American study on UESL.…”
Section: Outcomementioning
confidence: 99%
“…However, there were studies showing no improvement in outcomes associating with the use of chemotherapy [28] . In principle, adult-type NRSTS are usually assumed to be relatively insensitive to chemotherapy, with reported tumor response in the range of 40%-50%, or even less, and RT has a role in local control after incomplete resections and even after wide excisions in the case of large tumors [29] . Thus, our study further provides the evidence of RT and chemotherapy in the treatment of NRSTS, revealing RT is more appropriate for orbital NRSTS.…”
Section: Discussionmentioning
confidence: 99%
“…The additional value of HIPEC, regardless of regimen, remains unclear, and in view of the associated toxicity of HIPEC without a proven survival benefit, its use should be restricted to a very selected patient population and preferably within a study context.. The combination of induction chemotherapy, surgery, and WART has been included in the latest ‘Standard of Care and Treatment Recommendations’ for pediatric non-rhabdomyosarcoma soft tissue sarcoma from the European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%